On the Wave Energy Assessment in the South China Sea - Osinowo, Ayodotun; Lin, Xiaopei; Dongliang, Zhao; Zhifeng, Wang (Journal of Technology Innovations in Renewable Energy, 2016)
This paper presents a thirty year (1976-2005) assessment of wave energy resource within the South China Sea (SCS) by simulation. Significant wave height (SWH) between simulation and observation shows good agreement. This shows the reliability of an along-side simulated wave period in estimating wave energy in the SCS. Results show that estimates of wave power density are more reliable in the north-central SCS and most sufficient during winter. The annual mean wave power density peaked at 12.7kW/m and 12.9kW/m during years 1986 and 1999 respectively while the highest seasonal mean of 29kW/m occurred in year 1999 during winter. The wave power density is most stable in winter and is generally more stable in offshore regions of SCS. Wave power density is most stable in years 1976, 1997 and 2004 with stability values of 1.96, 1.98 and 1.9 respectively. The stability value of 0.9 in year 1980 is the greatest in the winter of all years. Relative-rich energy regions occupy the largest area during winter. The relatively richest energy is generally concentrated in the central and north-central SCS. No area is identified as a relative-rich energy region during spring. Winter 1999 has the highest relative-rich energy with value of 37kW/m.